2005
DOI: 10.1207/s15327949pac1101_3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Precision: Morality, Decision Making, and Collateral Casualties.

Abstract: Coalition aircraft [had] regularly been the target of hostile fire from the Deh Rawod area … Gunfire from various caliber weapons was observed throughout the day and at night, including mortars and AAA [anti-aircraft artillery] fire … Several compounds in the Deh Rawod area were positively identified as sources of this AAA fire. AAA fire had emanated from these compounds on repeated occasions over the previous two days and the source of the fires did not change. In all cases, the locations of these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This use of sanitizing language (see Bandura, 1999) is commonly found among deniers of wrongdoing (Bilali, Iqbal, & Freel, 2019;Parent, 2016) to explain that they had done the right thing despite civilian fatalities. These arguments support the idea that since security forces had already tried to minimize the harm to civilians, any such casualties were simply an unintended yet understandable consequence of the conflict (Roblyer, 2005).…”
Section: Discussionmentioning
confidence: 73%
“…This use of sanitizing language (see Bandura, 1999) is commonly found among deniers of wrongdoing (Bilali, Iqbal, & Freel, 2019;Parent, 2016) to explain that they had done the right thing despite civilian fatalities. These arguments support the idea that since security forces had already tried to minimize the harm to civilians, any such casualties were simply an unintended yet understandable consequence of the conflict (Roblyer, 2005).…”
Section: Discussionmentioning
confidence: 73%
“…Wolfe and Darley (2005) found that mechanisms such as cognitive dissonance and deindividuation came into play in situations where there was a protracted conflict and there was a need to distinguish civilians from combatants in situations where this distinction was not immediately clear. “Nation Partiality” (Roblyer, 2005) also meant that soldiers were more likely to see people in out-groups as all having the same views about the conflict and therefore all as potential enemies (Wolfe & Darley, 2005). In uncertain situations, minimizing losses from one’s own group became paramount, and soldiers may prioritize limiting these losses by, for example, harming enemy civilians (Hoge et al, 2004, Kooistra & Mahoney, 2016; Wolfe & Darley, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…If an act is deemed permissible under this condition, authorities must take measures to minimize civilian casualties, such as choosing alternative targets, choosing times or weapons that minimize civilian exposure, aborting attacks, or providing advance warning. However, these principles are open to interpretation, and whether a side is violating them is often disputed (Kreps, ; Roblyer, ; Tirman, ; Walzer, 2015; Wheeler, ).…”
Section: Civilian Casualties and Political Discoursementioning
confidence: 99%